"I say it but wouldn't be happy hearing it from a kid": Personal boundary parameters in responding to taboo language, swearing and -IST-ing use. (2022) - Downes, Lynn
Highlights: Swearing and taboo language use is changing in society. Policy responses in the institution of education have not changed. Language policy is structured as a behavior management issue in Queensland Australia. Policy relating to swearing and taboo language use is ambiguous. Participant responses are based on personal parameters rather than policy directives. Abstract: As a result of social and linguistic change, the use of swearing and taboo language has become commonplace in Anglophone societies with varying responses to its use. This commonplace use of swearing and taboo language is also apparent in educational institutions. Commentary from educators suggests they are frequently confronted with verbally abusive students in school settings. Data available in Queensland, Australia, illustrate a large percentage of students are suspended and excluded from school for verbal misconduct. As a result, many students are missing school because of institutionally unacceptable but socially and culturally mutable linguistic choices. This article examines the associated responses from stakeholders regarding swearing and taboo language use in school contexts, keeping the societal linguistic change in mind. Adopting a Foucaultian approach of discourse and power and Fairclough's Critical Discourse Analysis (CDA), 19 secondary school teachers were interviewed for their perspectives of and responses to the use of taboo language and swearing by secondary school students. Analysis of the data suggest three areas of concern. First, document analysis exposes ambiguity in the institutional behaviour management policies. Second, participant responses reveal limited knowledge of the policies and third, participants' use of personal parameters rather than policy when responding to swearing and taboo language use by students in school contexts. Therefore, policy needs to be readdressed with these data in mind and further studies relating to swearing and taboo language use in school contexts are required, specifically incorporating international perspectives, which may add insight to this linguistic issue. Short Abstract: As a result of social and linguistic change, the use of swearing and taboo language has become commonplace in Anglophone societies with varying responses to its use. Educational institutions demonstrate similar linguistic change, behaviour, and responses. Adopting a Foucaultian approach of discourse and power and Fairclough's Critical Discourse Analysis (CDA), 19 secondary school teachers were interviewed for their perspectives of and responses to the use of taboo language and swearing by students. Data analysis exposes ambiguity in institutional behaviour management policies, limited knowledge of policies by participants and the use of personal parameters by participants in responding to swearing and taboo language use by students in school contexts. Policy needs to be readdressed with these data in mind.